From the Street to the Web: Testimonies of the Artistic Protest of October 2019 and Its Continuity on Digital Platforms; [Calle a la Web: Testimonios Rotest Artística de Octubre 2019 y Su Continuidad en Las Plataformas Digitales] - Pizarro-Cortes, M (Universitat de Valencia, Faculty of Philology, Translation and Communication, 2024)
The revolt, outbreak or social revolution of October 2019 in Chile was a period of intense visual street manifestation, characterized by a proliferation of texts, images and testimonial performances. Attending to this phenomenon of significant overabundance, records were immediately generated, as well as publications and platforms aimed at preserving urban interventions, according to intentions and procedures of a contemporary archivistics. The aim of this article is to analyze, from the strategies they use, initiatives that digitally recover records of visual events of protest and integrate them into a larger and more complex unit: the repository Voces en el muro (UTEM), the photographic work La ciudad como texto (C. Ureta) and a chapter of the YouTube series Olvidarte nunca (CanalPo-brecitoMortal). These initiatives constitute open narratives that share four specific features: (1) they are third-order elaborations that integrate and resignify records of visual events; (2) they link the records to the precise space in which the visual event unfolds; (3) they generate a type of contact with the user of the interface that goes beyond passive observation and opens up the possibility of interaction; and (4) they account for the constructive process -both of the second-order record and of the platform- so that, to different degrees and measures, they expose how to do things with images. © 2024 Universitat de Valencia, Faculty of Philology, Translation and Communication. All rights reserved.